Knowledge and Preventive Practices among Construction Workers work in KTFT Project Regarding Occupational Health Hazards and Safety: A Descriptive Cross Sessional Study - Bhattarai, Anjana; Subedi, Pitamber (KTFT Journal, 2024)
This study investigates the knowledge and preventive practices regarding occupational health hazards and safety among construction workers engaged in the KTFT Project in Nepal. Occupational health hazards encompass a broad range of risks, including physical, chemical, ergonomic, and psychosocial factors, which can lead to injuries, illnesses, and fatalities in the workplace. Safety measures play a crucial role in mitigating these risks and ensuring the well-being of workers. Utilizing a mixed methods research design with a cross-sectional approach, data were collected from 124 construction workers and 2 safety engineers through face-to-face interviews and key informant interviews, respectively. The findings reveal that the majority of workers are male, predominantly within the age group of 20-39 years, with varying levels of education and ethnic backgrounds. Injuries and health issues such as musculoskeletal problems, skin-related issues, and respiratory problems are prevalent among the workers. The main causes of accidents include slipping, tripping, and falling, as well as injuries from lifting or carrying objects and falling objects. Regarding the level of knowledge and preventive practices, the study found that while most workers were aware of the common occupational hazards, their preventive practices were significantly good. Although a significant portion of the workers received some form of training and safety inspections were regularly conducted, gaps in the availability and use of Personal Protective Equipment (PPE) were noted. Furthermore, the research confirms that the KTFT Project soley incorporated labor law guidelines, highlighting compliance with regulatory standards. The research underscores the critical need for enhanced safety training, stricter enforcement of safety regulations, and better provision and utilization of PPE to improve occupational health and safety in the construction sector. These findings provide essential insights for policymakers and stakeholders to address the safety and health challenges faced by construction workers in Nepal.